Correlation between Noncompliance Behavior and Biochemical Parameters of Chronic Kidney Disease Patients Undergoing Hemodialysis - Fernandes, Sarita Telma; Dsouza, Sushma Marita (Journal of Health and Allied Sciences NU, 2021)
Background and Objectives Compliance with dietary, fluid, and medication instructions is a critically significant factor for the health and well-being of patients undergoing hemodialysis for an extended period. The current study assessed the correlation between noncompliance behavior and biochemical parameters of chronic kidney disease (CKD) patients undergoing hemodialysis. The study's objectives were 1) to assess patients' noncompliance behavior using a questionnaire, 2) to determine the biochemical parameters of CKD patients having noncompliance behavior, and 3) to find the correlation between biological parameters and noncompliance behavior.Methods A cross-sectional study was conducted from July 12, 2018, to February 10, 2019. A purposive sampling technique was used to recruit the participants, and 100 participants were included in the study. The End-Stage Renal Disease–Adherence Questionnaire was used to assess the non-compliance behavior.Results Most dialysis patients (70%) were compliant with the therapeutic regime, while 30% failed to comply. The study revealed a significant positive correlation between noncompliance behavior and biochemical parameters of CKD patients undergoing hemodialysis (r = 0.578, p < 0.05).Conclusion Noncompliance behavior is significantly correlated with the biochemical parameters among patients with CKD on dialysis. Optimal health is possible through fluid and dietary compliance in these patients. Hence, adherence behavior plays a significant role in the health and recovery of dialysis patients with CKD.
Keywords: biological parameter; chronic kidney disease; corelation; hemodialysis; noncompliance behavior